К археологической карте средневековых памятников восточной оконечности Керченского полуострова - Пономарев, Л.Ю. (Боспорские исследования, 2009)
The materials to the archaeological map of medieval monuments of the eastern extremety of the Kerch Peninsula are summarized. The region of research borders on the Mithradates range in the north, Lake Tobechik in the south, Ternovaya gully and Churubash gully, and Dzhankoisky Bugor tract in the west. The region occupies one hundred thirty five square kilometers. The medieval monuments were found there in the 30s of the 20th century for the first time. One hundred and three medieval monuments have been found by now in this territory, a city-site, settlements, graves with slabs facing their walls, underground graves with slabs, individual burials and ritual complexes among them. Five monuments are dated back to the 4th-5th (7th) cc. Seventy nine monuments are dated back to the 7th (8th) – the first half of the 10th century. Nineteen ones are dated back to the 13th-18th cc. Six coins come from here. History of five coins is unknown. The earliest coin is dated back to the time of Justin I, and the latest – to the time of Basil II and Constantine VIII (976-1025). No monuments which could be dated back to the second half of the 10th-the 12th cc. have been found yet. Nomad burials of that period have not been found either. The number of discovered medieval monuments will grow of course, as future research continues, but some of them are lost irreparably as the result of man-made influence and natural factors.